(untitled) (INSÓLITA - Revista Brasileira de Estudos Interdisciplinares do Insólito, da Fantasia e do Imaginário, 2026)
This article analyzes Jordan Peele’s Us (2019) through the figure of the double as an aesthetic and political operator of dystopia. In dialogue with Who Sings the Nation-State? by Judith Butler and Gayatri Spivak, it investigates how the pronoun “us,” inscribed in the film’s title, destabilizes naturalized notions of national belonging. The narrative projects into the present the ruins of liberal democracy, exposing physical and symbolic borders that produce “stateless” subjects within the nation. Drawing as well on Clément Rosset’s reflections on illusion, duplication, and the refusal of the real, the article reads monstrosity as an effect of the emergence of the excluded and of the collapse of utopian promises of unity. By recuperating the event Hands Across America as an anti-utopian parody, the film transforms the imaginary of national cohesion into an image of collective violence. The uncanny thus operates as a critique of the present, revealing dystopia not as a distant future but as a structural condition of the now.